Comparison of Pain with Subcutaneous Lignocaine Infiltration based on Gate-control Hypothesis versus Conventional Bleb Formation before Passing Large-Bore Intravenous Cannula - Rizwan, Muhammad; Majeed, Kaukab; Amjad Ali, Chaudhry; Hussain, Akhtar; Qureshi, Sajjad; Ansari, Kaswar Sajjad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To measure the frequency of pain with two techniques of local infiltration, i.e. local infiltration by raising bleb with help of local anesthetic, and rubbing the site of infiltration of local anesthetic.Study Design: Quasi-experimental study.Place and Duration of Study: Anesthesia Department, Combined Military Hospital, Quetta Pakistan, from Mar to Aug 2023.Methodology: A sample of 130 patients was divided into two equal groups: In Group-A, local anesthetic was infiltrated locally by raising a bleb and in Group-B, continuous rubbing was employed over infiltration site of local anesthetic. The frequency of pain was noted in both study group and Chi-square analysis was employed to compute statistical significance through                              p-value.Results: The numerical rating score (NRS) was higher in Group-A patients as 52(80.0%) patients had NRS >4 while 13(20.0%) had NRS4 while 46(70.8%) patients had NRS